2003
DOI: 10.1152/ajpcell.00339.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sequence mutations in teleost cardiac troponin C that are permissive of high Ca2+ affinity of site II

Abstract: Cardiac myofibrils isolated from trout heart have been demonstrated to have a higher sensitivity for Ca2+ than mammalian cardiac myofibrils. Using cardiac troponin C (cTnC) cloned from trout and mammalian hearts, we have previously demonstrated that this comparatively high Ca2+ sensitivity is due, in part, to trout cTnC (ScTnC) having twice the Ca2+ affinity of mammalian cTnC (McTnC) over a broad range of temperatures. The amino acid sequence of ScTnC is 92% identical to McTnC. To determine the residues respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…Scatchard plots of these data were used to determine K′ Ca . At 7°C, pH 7.0 the K′ Ca of the EGTA was 1.01 × 10 6 while at 30°C, pH 7.0 this value was 2.20 × 10 6 .…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Scatchard plots of these data were used to determine K′ Ca . At 7°C, pH 7.0 the K′ Ca of the EGTA was 1.01 × 10 6 while at 30°C, pH 7.0 this value was 2.20 × 10 6 .…”
Section: Methodsmentioning
confidence: 93%
“…Position y still has a hydrophobic residue, but negative residues before (Asp 30) and after (Glu 32) may provide alternative binding, in an unusual EF-hand conformation. Titration of a number of F27W ScNTnC mutants while monitoring fluorescence has demonstrated that both Gln 29 and Asp 30 are required for F27W ScNTnC to maintain its high affinity for Ca 2+ (6). This result suggests that both of these residues are involved in conferring ScNTnC its unique Ca 2+ binding abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies revealed myofibrils from fish (Churcott et al, 1994) and frog (Harrison and Bers, 1990) heart have a greater Ca 2+ sensitivity than those from the mammalian heart. This response, at least in fish, involves greater Ca 2+ sensitivity of the fish isoform of TnC (Gillis et al, 2003). Unfortunately the length-dependent change in myofilament Ca 2+ sensitivity has not been investigated in fish.…”
Section: Troponinsmentioning
confidence: 99%
“…The effects of temperature acclimation on cardiac contractility in ectotherms are well documented (Keen et al, 1994;Shiels and Farrell, 1997;Aho and Vornanen, 1999) (for a review, see Driedzic and Gesser, 1994). More recent work has focused on elucidating adaptations in cardiac myocyte excitability Paajanen and Vornanen, 2004), cellular Ca 2+ cycling Harwood et al, 2000, Shiels et al, 2000Shiels et al, 2002a;Shiels et al, 2002b;Hove-Madsen et al, 2003) and protein structure (Yang et al, 2000;Gillis et al, 2000;Gillis et al, 2003) associated with maintained cardiac viability in the cold (for reviews, see Vornanen et al, 2002b;Gillis and Tibbits, 2002). Although some ectotherms cope with cold temperatures via cold-torpor and resultant reductions in metabolic rate and heart rate, there are several compensative changes often associated with ectotherms that remain active in the cold.…”
Section: Introductionmentioning
confidence: 99%